(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objectives of this work were (i) to investigate thecontribution of the baobab tree (Adansonia digitata L., known locally as"tebeldi") fruits extraction in rural household’s income and tree speciesconservation and (ii) to identify and analyze the determinants of incomegeneration from A. digitata fruits extraction. Five villages were selectedin Rashad Locality, South Kordofan State, based on proximity gradient tothe resource. A sample of 276 households was taken from the selectedvillages, using a stratified sampling technique. Both quantitative andqualitative data were collected in 2009, using participatory rural appraisaltools. The results indicated that the household’s annual average incomefrom the A. digitata fruit sale was 44% of the total household income,aggregated across wealth categories. The results also showed that wealth,proximity to the resource and other household characteristics affected theincome generation from A. digitata fruit sale. It was concluded that the A.digitata fruits extraction plays a key role in improving the livelihood ofthe rural households and conserving the tree species. Rural developmentand future conservation interventions should pay attention to the role of A.digitata fruits extraction in rural economic development andenvironmental sustainability